2017
DOI: 10.1016/j.adolescence.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

A two‐year longitudinal study of gender differences in responses to positive affect and depressive symptoms during middle adolescence

Abstract: This study aimed to analyze the prospective associations during adolescence between depressive symptoms and response styles to positive affect and to examine gender differences. A longitudinal study was conducted with three waves separated by 1 year each to assess a non-clinical sample of 622 Spanish adolescents who were 13 and 14 years old (50.2% boys, 49.8% girls). The participants completed self-report measures of depressive symptoms and responses to positive affect (emotion-focused positive rumination, sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 92 publications
5
26
0
2
Order By: Relevance
“…Child characteristics, such as child gender, may also be important moderators in these processes. Prior studies have shown that girls dampen more than boys (Gentzler, Ramsey, Yi, Palmer, & Morey, 2014) particularly among adolescents, where 13-14-year-old boys' dampening decreased across two years but girls' increased (Gomez-Baya, Mendoza, Paino, & Gillham, 2017), and girls in ninth (but not seventh or eighth grade) dampened more than boys (Nelis, Bastin, Raes, & Bijttebier, 2018). The tendency for girls to dampen may have downstream effects on their later positive feelings and depression (Gentzler et al, 2014;Gomez-Baya et al, 2017;Nelis et al, 2018).…”
Section: Individual Difference Moderators: the Role Of Gender And Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Child characteristics, such as child gender, may also be important moderators in these processes. Prior studies have shown that girls dampen more than boys (Gentzler, Ramsey, Yi, Palmer, & Morey, 2014) particularly among adolescents, where 13-14-year-old boys' dampening decreased across two years but girls' increased (Gomez-Baya, Mendoza, Paino, & Gillham, 2017), and girls in ninth (but not seventh or eighth grade) dampened more than boys (Nelis, Bastin, Raes, & Bijttebier, 2018). The tendency for girls to dampen may have downstream effects on their later positive feelings and depression (Gentzler et al, 2014;Gomez-Baya et al, 2017;Nelis et al, 2018).…”
Section: Individual Difference Moderators: the Role Of Gender And Dmentioning
confidence: 99%
“…Prior studies have shown that girls dampen more than boys (Gentzler, Ramsey, Yi, Palmer, & Morey, ) particularly among adolescents, where 13–14‐year‐old boys’ dampening decreased across two years but girls’ increased (Gomez‐Baya, Mendoza, Paino, & Gillham, ), and girls in ninth (but not seventh or eighth grade) dampened more than boys (Nelis, Bastin, Raes, & Bijttebier, ). The tendency for girls to dampen may have downstream effects on their later positive feelings and depression (Gentzler et al, ; Gomez‐Baya et al, ; Nelis et al, ). Perhaps these gender differences emerge as a result of gender‐differentiated PA socialization, similar to studies examining gender‐specific NA socialization and its links to psychopathology (Brand & Klimes‐Dougan, ).…”
Section: Moving Forwardmentioning
confidence: 99%
“…Rates of depression increase in mid-adolescence compared to childhood and girls have been found to experience higher rates of depression than boys (Hankin et al, 2015;SAMHSA, 2012). Moreover, risks for depression may also operate differently depending on youth age or gender (Gentzler, Ramsey, Yi, Palmer, & Morey, 2014;Gomez-Baya, Medoza, Paino, & Gillham, 2017;Mezulis, Abramson, Hyde, & Hankin, 2004). Finally, we explored whether youth's value of happiness was related to socio-demographic characteristics (e.g., parent education or income) given how little is known about the value of happiness in youth.…”
Section: The Present Researchmentioning
confidence: 99%
“…First, the sample size did not allow for the effect of participant gender on central study variables to be explored. Given females reported significantly higher levels of YR-ES at Time 1 and a robust literature signaling gender differences in depression emerge during adolescence (Hankin et al 1998;Gomez-Baya et al 2017), such analyses would have been advantageous. Similarly, the sample size was insufficient to explore the contributions of specific positive self-schema themes to aspects of youths' functioning.…”
Section: Limitationsmentioning
confidence: 99%